2008
DOI: 10.1073/pnas.0710779105
|View full text |Cite
|
Sign up to set email alerts
|

The TLR3 signaling complex forms by cooperative receptor dimerization

Abstract: Toll-like receptors (TLRs) initiate immune responses by recognizing pathogen-associated molecules, but the molecular basis for recognition is poorly understood. In particular, it is unclear how receptor-ligand interactions lead to the initiation of downstream signaling. Here, we describe the mechanism by which TLR3 recognizes its ligand, double-stranded RNA (dsRNA), and forms an active signaling complex. We show that dsRNA binds saturably, specifically, and reversibly to a defined ligand-binding site (or sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
247
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(256 citation statements)
references
References 39 publications
8
247
1
Order By: Relevance
“…In addition, our molecular modeling studies revealed a topological basis for the interaction of 21-nt siRNAs with the active TLR3 dimer. In contrast, some structural studies have reported that efficient binding of dsRNA to TLR3 requires a minimum of 40-50 nt (16,37). The recent identification of a second binding site for dsRNA in TLR3 confirms the ability of 21-nt siRNA to bind this immune receptor (38) and helps to resolve some of the conflicting biological and structural data.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, our molecular modeling studies revealed a topological basis for the interaction of 21-nt siRNAs with the active TLR3 dimer. In contrast, some structural studies have reported that efficient binding of dsRNA to TLR3 requires a minimum of 40-50 nt (16,37). The recent identification of a second binding site for dsRNA in TLR3 confirms the ability of 21-nt siRNA to bind this immune receptor (38) and helps to resolve some of the conflicting biological and structural data.…”
Section: Discussionmentioning
confidence: 85%
“…TLRs comprise a family of innate immune receptors that recognize various pathogen-associated molecular patterns. TLR3 is a sensor of dsRNA (14), such as those found in viral genomes or replication intermediates, that undergoes dimerization (15)(16)(17)(18) and phosphorylation (19) to initiate a signaling cascade that can ultimately result in apoptotic cell death (20)(21)(22)(23). In this study, we sought to further explore this newly defined intersection between angiogenesis and innate immunity.…”
mentioning
confidence: 99%
“…TLR3 recognizes PV-RNA through the dsRNA-binding sites. Biochemical studies using in vitro-transcribed dsRNAs have shown that relatively long stretches of dsRNA (490 bp in length) are required for TLR3-mediated IFN-b promoter activation in HEK293/TLR3 cells and cytokine production from mouse myeloid DCs 11,27 . To determine the structural features of TLR3-activating or non-activating RNAs, the secondary structure of PV-RNAs was predicted using the mfold WebServer program, which calculates the minimum free-energy secondary structure 28 .…”
Section: Resultsmentioning
confidence: 99%
“…And, last, it was demonstrated that decoupling of the ECD and TIR of TLR4 from the TMD can disrupt its signaling [17] and that TLR4 constructs with the deleted ECD are constitutively active and dimeric [18]. Isolated TMDs of all TLR receptors were shown to homodimerize in bacterial membranes, with TMDs of TLR2, 3,8,9 having the highest propensity to perform homotypic interactions [19]. Taking into account all aforesaid, it is obvious that the structural investigations of TLR TMD dimers is necessary, because these domains can as well serve as targets for emerging therapies.…”
Section: Introductionmentioning
confidence: 99%
“…TLRs belong to the type I transmembrane proteins and consist of the extracellular ligand-binding domain extracellular domain (ECD), single transmembrane a-helix and intracellular Toll-interleukin I receptor domain (TIR), which is responsible for the downstream signaling [1,2]. According to crystal structures, TLRs form homo-or heterodimeric signaling complexes interacting with the single PAMP molecule [3][4][5][6][7]. The medical and biological significance of toll-like receptor (TLR) signaling is obvious, since the disregulation of the TLR system may cause various autoimmune diseases and septic shock [8][9][10][11], and some therapeutic strategies targeting TLRs have already emerged [8,11,12].…”
Section: Introductionmentioning
confidence: 99%